Medications and natural products used in Jordan for prevention or treatment of COVID-19 infection during the second wave of the pandemic: A cross-sectional online survey - Samar H. Thiab; Razan I. Nassar; Sara Thiab; Iman A. Basheti (Elsevier, 2022)
Worldwide, during the COVID-19 pandemic in 2019, there was an increase in the tendency of misusing prescription drugs as well as self-medicating with over-the-counters. Additionally, an increase in the use of herbs and natural products was reported. A descriptive cross-sectional survey was conducted in Jordan from May 19th to July 29th, 2021, to assess the medications and natural products used in Jordan during the second wave of the pandemic. The survey was developed and validated, then distributed using Google Forms via social media platforms. Data was analyzed using Statistical Package for Social Sciences-24. The study participants (n = 386) had a mean age of 29.35 (SD = 11.90) years. Most of participants were females (72.8%), not married (64.5%), non-smoker (69.2%), have a Jordanian nationality (80.6%), hold a bachelor's degree (73.1%), and living in the middle of Jordan (74.1%). More than 70% of the participants used vitamin C, D and pain relievers. The most used natural products were citrus fruits (78.8%), honey (63.0%) and ginger (53.1%). The participants reported that family and friends (55.4%) played a major role in advising them to use medications and dietary supplements. Pharmacists ranked second (54.1%), followed by social media platforms (43.3%). Multiple logistic regression analysis highlighted that only the age significantly affected the participants' use of medications and natural products (P < 0.001). The results of this study warrant the need of conducting awareness campaigns guided by trained healthcare providers to educate people and minimize the risk of side effects that may arise from unsupervised use of medications and natural products.